Pilot-scale testing of a leachbed for anaerobic digestion of livestock residues on-farm. (April 2016) - Yap, S.D.; Astals, S.; Jensen, P.D.; Batstone, D.J.; Tait, S.
Graphical abstract: Highlights: Pilot leachbeds compare leachate flow modes (trickling vs. flood-and-drain). Methane productivity is found to be insensitive to leachate flow modes. Leachbed performance was limited by microbial activity. Flood-and-drain mode mobilised unwanted non-degradable particulates into leachate. Trickling is to be preferred over flood-and-drain. Abstract: A leachbed is a relatively simple anaerobic digester suitable for high-solids residues and on-farm applications. However, performance characteristics and optimal configuration of leachbeds are not well-understood. In this study, two 200 L pilot-scale leachbeds fed with spent straw bedding from pigs/swine (methane potential, B0  = 195–218 L CH4  kg −1  VSfed ) were used to assess the effects of leachate recirculation mode (trickling vs. flood-and-drain) on the digestion performance. Results showed comparable substrate solubilisation extents (30–45% of total chemical oxygen demand fed) and methane conversion (50% of the B0 ) for the trickling and flood-and-drain modes, indicating that digestion performance was insensitive to the mode of leachate flow. However, the flood-and-drain leachbed mobilised more particulates into the leachate than the trickling leachbed, an undesirable outcome, because these particulates were mostly non-biodegradable. Inoculation with solid residues from a previous leachbed (inoculum-to-substrate ratio of 0.22 on a VS basis) hastened the leachbed start-up, but methane recovery remained at 50% of the B0 regardless of the leachate recirculation mode. Post-digestion testing indicated that the leachbeds may have been limited by microbial activity/inhibition. The high residual methane potential of leachate from the trickling (residual Bo  = 732 ± 7 L CH4  kg −1  VSfed ) and flood-and-drain leachbeds (582 ± 8 L CH4  kg −1  VSfed ) indicated an opportunity for further processing of leachate via a separate methanogenic step. Overall, a trickling leachbed appeared to be more favourable than the flood-and-drain leachbed for treating spent bedding at farm-scale due to easier operation.